The influence of different pathogens on the lysozyme activity into tissues of rat oral cavity - Levitsky, A. P.; Ostafiichuk, M. A.; Uspenskii, O. E.; Boris, G. Z.; Furdychko, A. I.; Ginzhul, I. V.; Vasiuk, V. L.; Stepan, V. T.; Iarynich, M. F.; Stupak, E. P. (Journal of Education, Health and Sport, 2017)
Aim: To determine action of the different pathogens on the lysozyme activity into tissues of oral cavity and serum. Methods: The lysozyme activities was determined into oral mucosa cheek, tongue gum and serum of 158 white rats (11 series experiments). The pathogens were used: atropine, protamine sulfat, indometacyn, bee poison, hydrasine sulfat, cytostatic cyclofosfan, lincomycin, lipopolysaccharide, composition of antibiotic and omeprasol for ACBT Results: The whole of pathogens decreased lysozyme activity (mean in 1,6-2,5 times) into oral tissues and on 16 % into serum. The specific lowering of lysozyme activities (Δ%/mg pathogen) was low most for lipopolysaccharide, especially after oral application usage (exceeding was in tens times). Conclusion: The lysozyme activity lowering may play significant role in pathogenesis of stomatologic diseases/ Lipopolysaccharide (LPS) send lysozyme activity lowering most especially after oral application. Probably, the antilysozyme action of pathogens realize by LPS. The stomatogenic factor in pathogenesis and profilactic of noninfection diseases is important.